Religion in The Midst of Polarization and A Crisis of Public Trust: The Reactualization of Tradition and State Intervention in Maintaining Coexistence in The Digital Era - Ahmad Murjoko (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2026)
Social polarization and crisis of trust in religious institutions and the state are strengthened in the digital age, exacerbated by algorithms that deepen identity fragmentation. This article formulates a key question: How can religion, through the reactualization of traditions and state intervention, maintain coexistence in the context of digital social disruption? The method used is a qualitative-critical approach through discourse analysis on religious policies, interfaith traditional practices, and digital narratives. The results of the study show that local religious traditions are able to support social cohesion in the midst of identity extremism. Meanwhile, state intervention in religious services of an ambivalent nature can be a facilitator of peace or a tool of symbolic domination. It was concluded that maintaining diversity today requires a synergy between the revitalization of cross-communal traditional values and the country's religious governance that is inclusive, equitable, and adaptive to the digital landscape. Religion will only play a constructive role if it is supported by the ethics of pluralism and digital civilization.